Voice Search SEO: Optimizing Marketing Strategies for the Future - Dewatmoko, Santo; Sonani, Nia; Sudrajat, Angga Pramadista (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research examines the relationship between Voice Search SEO optimization, Consumer Behavior Change, Natural Language Processing Technology, and Marketing Strategy Success in the context of PT. Yakult Indonesia Persada - Bandung 3. Using a quantitative research design with random sampling, the study collects data from 100 consumers to explore both direct and indirect effects among these variables. The analysis, conducted with SmartPLS, reveals significant direct effects from Voice Search SEO optimization to Marketing Strategy Success and Consumer Behavior Change to Marketing Strategy Success, indicating that voice search optimization and shifts in consumer behavior play crucial roles in marketing strategy success. Additionally, the results show that Natural Language Processing Technology mediates the relationships between Voice Search SEO optimization and Marketing Strategy Success, and Consumer Behavior Change and Marketing Strategy Success, suggesting that advanced Natural Language Processing Technology is instrumental in translating voice-based optimization and evolving consumer behaviors into successful marketing outcomes. The findings highlight the importance of adapting marketing strategies to align with voice search trends and evolving consumer preferences. Companies that invest in voice search SEO and Natural Language Processing Technology are better positioned to enhance customer experiences and achieve marketing success in a rapidly changing digital landscape. This research provides valuable insights for businesses seeking to remain competitive and meet the demands of a voice-driven consumer market.